Pengaruh Kualitas Jaringan, Kualitas Pelayanan, Emosional, dan Biaya Terhadap Kepuasan Pelanggan Pengguna Kartu Telkomsel - Rahmawati Rahmawati; Moch. Syauki; Cut Delsie Hasrina (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
This study aims to determine the effect of network quality, service quality, emotionality, and cost on customer satisfaction of telkomsel card users, either partially or simultaneously. the population in this study were telkomsel card customers in the village of Bukit Ewih Tamidelem. The sampling technique used was random sampling with a total sample of 87 people. The data analysis technique used is multiple linear regression analysis and for hypothesis testing, t-test and f-test are used. The results showed that: (1) the value of t-count> t-table (5.080>1.66298), then the results partially there is a positive influence between network quality on customer satisfaction. (2) The value of t-count> t-table (1.999 > 1.66298), then the results partially have a positive influence between service quality and customer satisfaction. (3) The value of t-count>t-table (4.672>1.66298), then the results partially have a positive influence between emotional and customer satisfaction. (4) The value of t-count>t-table (2.791>1.66298), then the results partially have a positive influence between costs and customer satisfaction. (5) Network quality, service quality, emotionality, and cost simultaneously affect customer satisfaction in the village of Bukit Ewih Tamidelem, Central Aceh district. With the value of f-count>f-table, that is (51.120>2.01). From the results of multiple linear regression equations, it can be seen that network quality, service quality, emotionality, and costs have a positive influence on customer satisfaction